Obesity - Haerens, Margaret (Detroit : Greenhaven Press, 2012)
"Obesity: The Global Obesity Epidemic; Obesity Factors; Obesity Effects; Anti-Obesity Policies"-- Provided by publisher
Includes bibliographical references (p. 210-212) and index
Keywords: Obesity -- Juvenile literature